Immersive models from analogical sketches applied to solimene’s factory - Rossi, Adriana (2018)
An experience for cultural heritage's survey with immersive hybrid (analogical-digital) models, created from in-the-place handmade sketches is presented. The recently developed cube and equirectangular methods will be used, looking for a balanced approach between the spontaneous personal impressions (architectural / sensitive vision), and the support of an objective-deep knowledge of immersive space representation (engineering / mathematical vision). The cube method, or T-cross method, starts from six square sketches (one from each face of a watchercentered ideal cube) that will be disposed in a T-cross grid to build from there an equirectangular image using digital tools. In order to create the immersive model, some metadata must be added ‘tricking’ the computer. The processed image will be considered, from there, like a native spherical photographic panorama. Loading this model in internet, the user will have, not just the possibility to simply navigate into the panorama using the browser or social medias, but to navigate into VR mode as well. On another hand, for the equirectangular method, the work must start directly from the equirectangular perspective structure. Then, a high complex piece of representation is generated, result of the first intuitioned / experiences improved with the application of math-based guidelines. The user, by digitalizing this sketch, can directly pass to metadata addition and share phases. The case study concerns to the “Solimene’s Factory”, work of Paolo Soleri architect and located in Vietri sul Mare, Italy. The building compones the UNESCO’s list of humanity’s cultural heritage. Aligned with an innovative geometrical analysis and documentation work, a fresh vision of the building, using tools up to today in develop for spherical sketches is given. In order to give a contemporary instrument for compless architecture reconstruction to space’s professionals, the main goal is to debug these immersive hybrid model generation methods. To do that, methods will be compared and synthetized by their experimented difficulties, founded solutions, vantages and updated guidelines.